Advancing Arabic Learning in the Society Era 5.0: Motivation Challenges for Indonesian Students in Jeddah - Aminuzal, Ikmal; Madjid, Muh. Naim; Putra, Yunis Eka (Arabi : Journal of Arabic Studies, 2024)
Human reliance on the flow of globalization and technology in Society Era 5.0 poses problems in the education field, which is progressively growing. Resolving urgent societal problems heavily relies on science and technology. Creative and innovative learning strategies have become crucial for overcoming student Arabic learning motivation. Based on observation, the researcher saw that the motivation of students to learn Arabic was relatively high. This researcher aims to analysis the motivation for Arabic learning among students in the Indonesian School of Jeddah based on the interview and questionnaire. The interview results reveal that four students said they were interested in learning Arabic, and two students were interested in learning other languages. Results in the pie-chart indicate 57,1% of respondents agree, 22,9% strongly agree, and 17,1% disagree with student motivation in Arabic learning. However Arabic learning at school still uses classical methods, irrelevant materials, and the language environment.